2018
DOI: 10.1007/s10029-018-1804-2
|View full text |Cite
|
Sign up to set email alerts
|

IPOM: history of an acronym

Abstract: IPOM has become a common term used by hernia surgeons. It refers to the treatment of a ventral hernia using an intraperitoneal placed mesh and most consider it an acronym for Intra-Peritoneal Onlay Mesh. Since intraperitoneal placement of mesh has fallen out of favor with some hernia surgeons and key-opinion-leaders recently, this might be the correct time to write down and preserve the history of this intriguing acronym.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…There is acceptable evidence that umbilical and epigastric hernias can be repaired safely using a synthetic polypropylene mesh 30,37,48,60,61 . Similar to incisional hernias, there are five theoretical anatomical layers for mesh placement: onlay, in the prefascial plane above the linea alba; fixing the mesh to the borders of the repair (inlay plug); retromuscular, between the rectus muscle and the posterior rectus sheath; preperitoneal, between the posterior rectus sheath and the peritoneum; and intraperitoneal, also called intraperitoneal onlay mesh (IPOM) 62,63 .…”
Section: Quality Of Evidence: Strength Of Recommendation: Weakmentioning
confidence: 99%
“…There is acceptable evidence that umbilical and epigastric hernias can be repaired safely using a synthetic polypropylene mesh 30,37,48,60,61 . Similar to incisional hernias, there are five theoretical anatomical layers for mesh placement: onlay, in the prefascial plane above the linea alba; fixing the mesh to the borders of the repair (inlay plug); retromuscular, between the rectus muscle and the posterior rectus sheath; preperitoneal, between the posterior rectus sheath and the peritoneum; and intraperitoneal, also called intraperitoneal onlay mesh (IPOM) 62,63 .…”
Section: Quality Of Evidence: Strength Of Recommendation: Weakmentioning
confidence: 99%
“…The reason behind this could be multiple stress to abdominal wall or surgical procedure involved in delivery 14 . Traditionally the laparoscopic technique needs mesh which cover peritoneal cavity as seen on this study as well with pre-suture closing [15][16][17] . The present study results showed that laparoscopic procedure had short hospital stay, less chances of recurrence and minimal wound infection chances.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, a laparoscopic ventral hernia repair has been performed with an intraperitoneal onlay mesh (IPOM). With this procedure, a coated mesh is placed intra-peritoneally and fixated with tackers [ 10 ]. The procedure is easy to learn with good short-term outcomes; however, concerns about long-term complications to the intraperitoneal mesh and chronic pain due to mesh fixations have arisen [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%